2023
DOI: 10.1021/acsanm.2c05227
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Hexaferrite Ceramic Magnets Made from Nanoplatelets of Ferrihydrite by High-Temperature Calcination for Permanent Magnet Applications

Abstract: Highly aligned ceramic hexaferrite magnets with high-energy products (BH) max and a density exceeding 90% of theoretical density have been fabricated. The precursors were an antiferromagnetic powder, a six-line ferrihydrite mixed with SrCO 3 , and a grain growth inhibitor SiO 2 . Conventional cold compaction of the precursor powders was employed prior to calcination at temperatures of 1050, 1150, and 1250 °C. The influence of calcination temperature and magnetic properties has been systematically studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recently, Vijayan et al reported the use of SPS not only for densification of ferrite powders but for the direct synthesis of aligned SrM magnets [75][76][77]. In this study, SrM is synthesized directly during the SPS process using a precursor powder of antiferromagnetic six-line ferrihydrite (FeOOH) platelets mixed with SrCO 3 .…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
“…Recently, Vijayan et al reported the use of SPS not only for densification of ferrite powders but for the direct synthesis of aligned SrM magnets [75][76][77]. In this study, SrM is synthesized directly during the SPS process using a precursor powder of antiferromagnetic six-line ferrihydrite (FeOOH) platelets mixed with SrCO 3 .…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%